Mekanisme Pembiayaan Berbasis Digital pada Fintech Syariah Peer To Peer Lending - Hanim Misbah; Saiful Bakhri; Risa Umami; Kharina Arifia (Tasharruf : Journal of Islamic Economics and Business, 2025)
The rapid advancement of information technology has significantly transformed financial services, giving rise to digital innovations such as Islamic Peer-to-Peer (P2P) Lending Fintech. This platform offers a Sharia-compliant financing alternative, primarily targeting Micro, Small, and Medium Enterprises (MSMEs) that often face barriers in accessing traditional bank loans. This study aims to analyze the digital financing mechanism within Islamic P2P lending, examining its regulatory framework, underlying Islamic contracts, operational structure, and key distinctions from conventional models. The findings indicate that Islamic P2P lending operates on core Sharia principles prohibiting riba (usury), gharar (uncertainty), and maysir (speculation) and utilizes contracts such as mudharabah (profit-sharing), musyarakah (joint venture), wakalah bil ujrah (fee-based agency), and al-qardh (benevolent loan). The study concludes that Islamic P2P lending enhances financial inclusion by providing accessible, transparent, and ethically structured digital financing, thereby supporting the growth of MSMEs and promoting the broader development of Indonesia's Islamic financial ecosystem.